2020
DOI: 10.2147/ibpc.s280763
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Profiles and Correlation with Cardiovascular Risk Factors in a Sample of 390 University Employees in Tanzania

Abstract: Background Hypertension is a major risk factor for cardiovascular morbidity and mortality. Increasingly, evidence suggests that 24-hour ambulatory blood pressure (BP) monitoring (ABPM) is more accurate than clinic BP in predicting cardiovascular risk. However, this association has not been widely studied in subSaharan Africa, especially in Tanzania. Aim To explore the relationship between 24-hour ABPM profiles and cardiovascular risk factors in comparison with clinic BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(71 reference statements)
3
1
0
Order By: Relevance
“…Regarding 24-hour mean diastolic BP, we found significant correlations with BMI and prior stroke, consistent with previous research [13,16]. The inverse relationship between diastolic BP and cardiovascular risk, particularly coronary heart disease, was well-established [17,18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding 24-hour mean diastolic BP, we found significant correlations with BMI and prior stroke, consistent with previous research [13,16]. The inverse relationship between diastolic BP and cardiovascular risk, particularly coronary heart disease, was well-established [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…Chuwa et al conducted a study in Tanzania, involving university employees, and reported similar correlations, except for family history of hypertension [13]. Furthermore, the prevalence of dyslipidemia in our study population was consistent with previous findings, supporting the correlation between dyslipidemia and elevated BP [13]. These results indicate the relevance of considering these factors in assessing an individual's BP and cardiovascular risks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Twenty-four-hour ambulatory blood pressure monitoring (ABPM) provides information about the blood pressure profile and its variability, unlike office measurements. ABPM parameters (including daytime and nighttime systolic blood pressure (SBP), diastolic blood pressure (DBP), standard deviation, and dipping status) correlate more strongly with the risk of cardiovascular diseases and cardiovascular death than office blood pressure [3][4][5][6][7][8]. ABPM allows for the evaluation of short-term blood pressure variability.…”
Section: Introductionmentioning
confidence: 99%